OTIMIZAÇÃO DA FERMENTAÇÃO ALCÓOLICA DO EXTRATO AQUOSO DA POLPA DE JERIVÁ (Syagrus romanzoffiana) - Maia, Guilherme Arielo Rodrigues (2013)
Brazil is one of the most advanced countries, in the technological point of view, regarding the production and use of ethanol as fuel. It is used mostly in the gasoline blend, and is applied to exclusive use of direct fuel. In order to obtain it, different types of biomass can be explored, and sugar cane is both the main source of fuel generation. In the process of ethanol production, many factors may cause interference in expected yields. The aim of this study was to determine the best process conditions for fermentation of aqueous jerivá pulp extract using the response surface methodology and optimization simplex. Design was incomplete factorial 33 with yeast extract, yeast and NH4H2PO4 as independent variables and ethanol yield, the response. Regression analysis showed that the model is predictive and the simplex optimization indicated a formulation containing 0.35 g L-1 yeast extract, 6.33 g L-1 yeast and 0.30 g L-1 and NH4H2PO4, for an optimum yield of 85.40% ethanol. To validate the predictive equation, experiment was repeated in triplicate under optimum conditions, yielding, and an average yield of 87.15% was obtained. According to application of the t test, it was found that there was no significant difference, at 5% level, between the mean value obtained and the value obtained by simplex optimization.